2010
DOI: 10.1074/jbc.m109.085100
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of Phospholipase C-β2 Activity and Membrane Interaction by Gαq, Gβ1γ2, and Rac2

Abstract: We combined fluorescence recovery after photobleaching (FRAP) beam-size analysis with biochemical assays to investigate the mechanisms of membrane recruitment and activation of phospholipase C-␤ 2 (PLC␤ 2 ) by G protein ␣ q and ␤␥ dimers. We show that activation by ␣ q and ␤␥ differ from activation by Rac2 and from each other. Stimulation by ␣ q enhanced the plasma membrane association of PLC␤ 2 , but not of PLC␤ 2 ⌬, which lacks the ␣ q -interacting region. Although ␣ q resembled Rac2 in increasing the contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 63 publications
(118 reference statements)
4
29
0
Order By: Relevance
“…These affinity measurements are supported by a recent crystal structure of full-length PLC-␤3 and G␣ q showing minimal interaction between G␣ q and the C-terminal domain (18). Nevertheless, G␣ q -dependent activation of PLC-␤ isozymes at membranes clearly is supported by the C-terminal domain (23)(24)(25). Whereas it is reasonable to posit that membranes facilitate interactions between the C-terminal domain and G␣ q to support phospholipase activity, the nature of these potential interactions remains poorly understood.…”
supporting
confidence: 60%
See 2 more Smart Citations
“…These affinity measurements are supported by a recent crystal structure of full-length PLC-␤3 and G␣ q showing minimal interaction between G␣ q and the C-terminal domain (18). Nevertheless, G␣ q -dependent activation of PLC-␤ isozymes at membranes clearly is supported by the C-terminal domain (23)(24)(25). Whereas it is reasonable to posit that membranes facilitate interactions between the C-terminal domain and G␣ q to support phospholipase activity, the nature of these potential interactions remains poorly understood.…”
supporting
confidence: 60%
“…The C-terminal domain also enhances the propensity of PLC-␤ isozymes to associate with membranes. This property was suggested by early cell fractionation studies showing shifts from particulate to soluble fractions of PLC-␤ isozymes that lacked an intact C-terminal domain (24,25). More recent fluorescent microscopy studies highlight the intrinsic propensity of this region to associate with cellular membranes, which is consistent with the observation that the C-terminal domain is highly electrostatically polarized along its long axis (50).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Baculoviruses containing cDNA for the human Gα i2 protein subunit [17] were donated from Professor Alfred G. Gilman (University of Texas Medical Center, Dallas, TX, USA), and baculoviruses containing cDNAs for the human Gβ 1 and bovine Gγ 2 subunits [18] were provided by Prof. Dr. Peter Gierschik (Institute of Pharmacology, University of Ulm). Cells were cultured at 27°C in Insect Xpress media (Lonza Group, Basel, Switzerland) containing 0.1 mg/ml of gentamicin.…”
Section: Protein Expression In Sf 9 Insect Cells and Membrane Preparamentioning
confidence: 99%
“…PLCb is activated by members of the Gaq family of G proteins (12), such as Ga11 (13) and Gaq (14). It was suggested that Ga11 acts upstream of PLCb activation in Jurkat T cells (8).…”
Section: Seb-induced Steroid Resistance Depends On Activation Of Gaqmentioning
confidence: 99%